2021
DOI: 10.1029/2020jd032895
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Westward‐Propagating Semidiurnal Tides and Their Composite Response to Sudden Stratospheric Warmings in SuperDARN and SD‐WACCM‐X

Abstract: Using the Super Dual Auroral Radar Network observations (clustered around 60°N) and NCAR CESM2.0 extended Whole Atmosphere Community Climate Model nudged with reanalyzes, we examine the climatology of semidiurnal tides in meridional wind associated with the migrating component (SW2) and non‐migrating components of wavenumbers 1 (SW1) and 3 (SW3). We then illustrate their composite response to major sudden stratospheric warmings (SSWs). Peaking in late summer and winter, the climatological SW2 amplitude exceeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…Zhang et al. (2021) also found improved agreement between high latitude zonal winds simulated by SD‐WACCM‐X and observed by radars in the first 2 weeks following SSW onset. However, as these particular major SSWs persist, the model winds in the MLT turn easterly after about 10 days but remain westerly in the observations.…”
Section: Climatology Of Model‐measurement Zonal Wind Differencesmentioning
confidence: 78%
See 1 more Smart Citation
“…Zhang et al. (2021) also found improved agreement between high latitude zonal winds simulated by SD‐WACCM‐X and observed by radars in the first 2 weeks following SSW onset. However, as these particular major SSWs persist, the model winds in the MLT turn easterly after about 10 days but remain westerly in the observations.…”
Section: Climatology Of Model‐measurement Zonal Wind Differencesmentioning
confidence: 78%
“…One of the most widely used models is the Whole Atmosphere Community Climate Model (WACCM) (Marsh et al., 2013). Unfortunately, there is a limitation to using WACCM as a tool to study these processes in the polar winter mesopause region because it has a well‐known easterly (westward) wind bias in the polar winter upper mesosphere (e.g., Eswaraiah et al., 2016; Harvey et al., 2019; Hindley et al., 2022; Lieberman et al., 2015; Liu, 2016; Marsh et al., 2013; Noble et al., 2022; Rüfenacht et al., 2018; Smith, 2012; Yuan et al., 2008; Zhang et al., 2021). This bias is not unique to WACCM, and other comprehensive high‐top general circulation models with parameterized GWs show the same deficiencies in simulating the observed zonal wind structure (e.g., Wilhelm et al., 2019) in the winter upper mesosphere (e.g., Griffith et al., 2021; McCormack et al., 2017, 2021; McLandress et al., 2006; Pedatella, Fuller‐Rowell, et al., 2014; Schmidt et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was made by Tomikawa et al (2012) who showed that a model with a top at 85 km can be sufficient to model the dynamics of elevated stratopause events. In addition, even in models extending into the lower thermosphere, the stratopause reforms -on average-at lower altitudes than 80 km: near 75 km in the composite of 13 ESEs in SD-WACCM (extending up to 140 km) (Limpasuvan et al, 2016), or in the composite of 9 ESEs in SD-WACCM-X (extending up to 400 km) (Zhang et al, 2021).…”
Section: Model Data and Methodsmentioning
confidence: 99%
“…The numerical study of the SW2 tide has a long history (e.g., Forbes & Garrett, 1979). Nevertheless, open questions remain about the mechanisms governing the tide's seasonal and short‐term variability (Conte et al., 2018; G. Liu et al., 2021; Pedatella et al., 2020; Zhang et al., 2021). Many recent studies are in part driven by the increasing availability of high‐altitude and tide‐resolving general circulation models.…”
Section: Introductionmentioning
confidence: 99%